2013
DOI: 10.4244/eijv8i9a155
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and angiographic experience with a third-generation drug-eluting Orsiro stent in the treatment of single de novo coronary artery lesions (BIOFLOW-I): a prospective, first-in-man study

Abstract: The Orsiro drug-eluting stent demonstrated potency with low rates of in-stent neointimal hyperplasia and cardiovascular events but warrants further evaluation in a larger population cohort with longer follow-up time points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 12 publications
1
36
0
Order By: Relevance
“…Slower polymer degradation or thinner stent struts may reduce the inflammatory response and the risk of early 29,30 and progressively thinner strut profiles. 13,31,32 Thin stent struts have been associated with less wall shear and thrombogenicity, 33 which may be an explanation for the lower stent thrombosis rate in the SORT OUT VII despite that thinner stent struts may be more prone to longitudinal compression 34 and to an increased risk of tissue prolapse intensifying thrombogenicity. 35 In head-to-head randomized trials, the biodegradable polymer stents have shown noninferiority to the durable flouropolymer everolimus-eluting stent 13,14 and the first-generation sirolimus-eluting stent 15 within the first year after stent implantation, whereas the biolimus-eluting Nobori stent failed to show noninferiority within 1 year in the SORT OUT V trial.…”
Section: Downloaded From Sirolimus-eluting Vs Biolimus-eluting Biodegmentioning
confidence: 99%
See 1 more Smart Citation
“…Slower polymer degradation or thinner stent struts may reduce the inflammatory response and the risk of early 29,30 and progressively thinner strut profiles. 13,31,32 Thin stent struts have been associated with less wall shear and thrombogenicity, 33 which may be an explanation for the lower stent thrombosis rate in the SORT OUT VII despite that thinner stent struts may be more prone to longitudinal compression 34 and to an increased risk of tissue prolapse intensifying thrombogenicity. 35 In head-to-head randomized trials, the biodegradable polymer stents have shown noninferiority to the durable flouropolymer everolimus-eluting stent 13,14 and the first-generation sirolimus-eluting stent 15 within the first year after stent implantation, whereas the biolimus-eluting Nobori stent failed to show noninferiority within 1 year in the SORT OUT V trial.…”
Section: Downloaded From Sirolimus-eluting Vs Biolimus-eluting Biodegmentioning
confidence: 99%
“…suggested as a trigger for a chronic inflammatory response, 10,11 and third-generation coronary DESs [12][13][14][15] with biodegradable polymers have been designed to overcome concerns over the delayed arterial healing, which might increase the risk of late stent thrombosis and restenosis. Third-generation biolimuseluting stent was designed with a biodegradable polymer.…”
Section: Sirolimus-eluting Vs Biolimus-eluting Biodegradable Polymer mentioning
confidence: 99%
“…11 Pharmacokinetic studies attested to adequate drug release and tissue retention in vivo, and experimental studies showed inflammatory scores comparable to bare metal stents during long-term follow-up throughout 6 months. 12 Following results of a firstin-man study comprising 30 patients, 13 the Biotronik-Safety and Clinical Performance of the Drug Eluting Orsiro Stent in the Treatment of Subjects With Single De Novo Coronary Artery Lesions-II (BIOFLOW-II) trial was designed to directly compare the angiographic efficacy of the novel biodegradable polymer-based sirolimus-eluting Orsiro stent (O-SES) with the durable polymer-based everolimus-eluting Xience Prime stent (X-EES) platform in a randomized, multicenter, assessor-blind, noninferiority trial. Our primary hypothesis was that O-SES is not inferior to X-EES in terms of the primary end point LLL at 9 months.…”
mentioning
confidence: 99%
“…Finally, the BIOFLOW-I was a first-in-man study evaluating the efficacy and safety of the Orsiro BP-SES in 30 patients with single de novo native coronary lesions. 26 Angiographic in-stent LLL was 0.05±0.22 mm at 9-month follow-up; at 12 months, the cumulative incidence of device-oriented major adverse cardiovascular events was 10%; no ST was observed. The current study in non-diabetic patients with ACS demonstrated better OCT-detected neointimal strut coverage associated with the Orsiro BP-SES compared with DP-ZES at 3 months.…”
Section: Discussionmentioning
confidence: 99%